Future of total hip arthroplasty with the Metha short stem in modern surgeries - Marek Drobniewski; Marek Synder; Marek Aleksander Synder; Magdalena Krasińska; Lukasz Olewnik; Andrzej Borowski (Scientific Reports, 2021)
Abstract The aim of the study was to analyse the results of uncemented total hip replacement, using the Metha (metaphyseal) stem. A total of 158 patients (70 females and 88 males) were qualified to the study and submitted to total hip arthroplasty (183 procedures altogether), using the Metha stem. The mean age of the patients on the day of surgery was 51.7 years (the range from 17 to 69 years). The mean follow up period was 9.2 years (the range from 5 to 13.5 years). Preoperative assessments gave poor scores, according to the Merle d’Aubigne and Postel classification, modified by Charnley. The average improvement after surgery, according to the used scale, was 6.9 points. A very good outcome was recorded in 154 cases (84.2%), a good outcome was achieved in 20 cases (10.9%) and a poor outcome was confirmed in 9 cases, while no satisfactory case was observed. Poor outcomes were associated with implant loosening. Extraskeletal ossification was noted in 10 cases (5.5%). According to the Kaplan–Meier estimator, the 10-year survival was 93.2% and 97.3% for the whole implant and the stem alone, respectively. 1. Our follow-up period of more than 9 years on the average, indicates that Metha stems produce excellent clinical and functional results in operated young patients with advanced degenerative changes of the hip joint. 2. Assuming a proper qualification for the procedure, the absence of complications and a correct surgical technique, which is slightly more difficult, when compared to standard stem implantation, the risk of aseptic loosening is fairly negligible.